Effect of High Temperature Per se on Growth Performance of Broilers - Abu-Dieyeh, Ziad Hamdan Mahmod (International Journal of Poultry Science, 2005)
Thirty two 4-wk-old broiler birds were grown in individual cages in two controlled-environmental chambers at 2 constant ambient temperatures (20 ±1oC Vs 35 ±1oC) until 8 wk of age. They were equally distributed into three treatments: 20oC, ad libitum feed consumption (20oC AL); 35oC, ad libitum feed consumption (35oC AL), and 20oC, pair-feeding on the daily feed intake of heat-exposed broiler birds. Water was provided for ad libitum consumption throughout the experimental period, which was lasted for 4 weeks. Body weight, feed intake, and feed conversion ratio were significantly reduced in broilers in heat stress group. At the same feed intake level (20oC PF Vs 35oC AL), heat-exposed birds gained less body weight and had significantly poorer feed conversion ratio (FCR). Moreover, rectal temperature and respiratory rate were significantly higher in heat stress group. These results indicated that high ambient temperature per se has a significant effect on growth rate depression rather than reduction in feed intake of heat exposed broilers.